2019
DOI: 10.1371/journal.pone.0220121
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment of ruptured cerebral aneurysms discovered using data driven analysis of gene expression

Abstract: Background It is well known that ruptured intracranial aneurysms are associated with substantial morbidity and mortality, yet our understanding of the genetic mechanisms of rupture remains poor. We hypothesize that applying novel techniques to the genetic analysis of aneurysmal tissue will yield key rupture-associated mechanisms and novel drug candidates for the prevention of rupture. Methods We applied weighted gene co-expression networks (WGCNA) and population-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Along with the development of bioinformatic tools appeared a new type of study presenting re-analyzed data from available datasets, including expression data from the Gene Expression Omnibus (GEO). Approximately one third of these published secondary analyses utilized a single dataset [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] and two thirds leveraged data from two to eight datasets [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. These studies did not provide any new additional clinical data but rather aimed to deepen the insight into molecular mechanisms of the IA pathophysiology by revealing key regulatory networks and interactions between investigated molecules.…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the development of bioinformatic tools appeared a new type of study presenting re-analyzed data from available datasets, including expression data from the Gene Expression Omnibus (GEO). Approximately one third of these published secondary analyses utilized a single dataset [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] and two thirds leveraged data from two to eight datasets [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. These studies did not provide any new additional clinical data but rather aimed to deepen the insight into molecular mechanisms of the IA pathophysiology by revealing key regulatory networks and interactions between investigated molecules.…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%
“…In some of these studies, specific areas of interest were predefined, such as: epithelial–mesenchymal transition [ 78 ], endoplasmic reticulum stress [ 81 ], immune environment [ 79 , 83 ], or ferroptosis [ 84 , 85 ]. In three studies, an attempt was made to identify potential therapeutic targets [ 71 , 82 , 83 ]. Sun et al investigated expression profiles and networks in various aneurysms, including thoracic and abdominal aorta aneurysms [ 77 ].…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%
“…Nakaoka et al 8 identified therapeutic targets for unruptured IAs. Landry et al 9 demonstrated for the first time the immune mechanism of IA rupture and new drug candidates. Whether EMT plays an important role in the progression of aneurysm is worthy of further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside crucial genes, Bo et al identified several crucial miRNAs as mediators of IA pathogenesis (19). Additionally, Landry et al combined WGCNA and population-specific gene expression analysis (PSEA) to analyze the microenvironment associated with ruptured IA (20). Although WGCNA has partially elucidated the pathogenesis of IA, the crucial genes mediating the rupture of IA require exploration.…”
Section: Introductionmentioning
confidence: 99%